2013
DOI: 10.1007/s11250-013-0412-5
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the horse and financial impact of equine trypanosomiasis on cattle raising in Venezuela

Abstract: In Venezuela, horses are indispensable for extensive cattle raising, and extensive cattle raising prevails in all regions. This determines the numerical relationship between horses and cattle (r = 0.93) to be relatively constant nationwide. At regional level, the average extension of cattle ranches varies greatly. However, in relation to the area covered by pastures, the numbers of horses (r = 0.95) and cattle (r = 0.93) are relatively uniform nationwide. Water buffalo occupy small fractions of the territory; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…As a result, these animals are in close contact where horses (susceptible hosts) coexist with cattle (low susceptibility reservoirs) and wild animals (reservoirs). This determines the numeric relation between horses and cattle with an r = 0.93, which is relatively constant in the whole country (Moreno et al 2013). This interaction could contribute to the dynamics and maintenance of trypanosomosis in the studied areas, which makes necessary the application of treatments for the effective control of the disease preventing the appearance of outbreaks in susceptible hosts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, these animals are in close contact where horses (susceptible hosts) coexist with cattle (low susceptibility reservoirs) and wild animals (reservoirs). This determines the numeric relation between horses and cattle with an r = 0.93, which is relatively constant in the whole country (Moreno et al 2013). This interaction could contribute to the dynamics and maintenance of trypanosomosis in the studied areas, which makes necessary the application of treatments for the effective control of the disease preventing the appearance of outbreaks in susceptible hosts.…”
Section: Discussionmentioning
confidence: 99%
“…In some occasions, outbreaks in goats, sheep and cattle livestock produced by T. vivax have been reported in the States of Falcón and Zulia, with a prevalence of 60 and 78 %, respectively, determined through direct microscopic examination (García et al 2000;Simoes et al 2009) and in horses by T. evansi in the State of Apure, with an active infection of 5.5-12 % (García et al 2000). Horses are essential for the management of cattle; thus, it is thought that equine trypanosomosis has an important negative impact on Venezuelan beef production (García et al 2000;Castellanos et al 2010;Forlano et al 2011;Moreno et al 2013). Recent studies in Venezuela estimated US$ 7,486,000 in losses, because of for the lack of diagnosis and adequate treatment for trypanosomosis in horses (Moreno et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information available for the Llanos of Venezuela indicates that ∼7% of horses suffer active infection with T. evansi ( García et al, 2000; Castellanos et al, 2010; Forlano et al, 2011 ). It has been calculated that losses owing to horse mortality caused by this hemoparasitosis would have amounted to US$ 7,486,000 for this region in 2008 ( Moreno et al, 2013 ). García et al (2005) have shown by bloodsmear examinations, microhaematocrit centrifugations and immunological assays that 6.7%, 11.4% and 39.5% of Venezuelan blood samples from water buffaloes and other livestock contained trypanosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Our stock of T. evansi (TeAp-N/D1) ( Perrone et al 2009 ) originated from horses in the Venezuelan Llanos region, where equine trypanosomiasis is endemic ( Moreno et al 2013 ). We cultured parasites in Sprague-Dawley rats inoculated intraperitoneally with 100 µL of rat blood containing live T. b. evansi at a concentration of 3.6 × 10 8 parasites/mL.…”
Section: Methodsmentioning
confidence: 99%